2017
DOI: 10.4103/0019-5413.201702
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of lower limb musculoskeletal trauma with associated vascular injuries in a tertiary care institute in India

Abstract: Background:Vascular trauma associated with bony injuries is an orthopaedic emergency. Lack of timely intervention can lead to loss of limb or even life. Inspite of the rising incidence of high speed road traffic accidents in India, there is paucity of literature regarding the demographic pattern, clinical morbidity, management strategies and outcome of arterial injuries associated with lower limb trauma. The aim of this study is to describe the epidemiology and outcome of lower extremity musculoskeletal trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…Such injuries are likely to have a major economic impact on young families. Similar data has been reported in other regional and international studies on injuries to PAs (1,2,3,4). Preventive measures targeting vulnerable motorcyclist needs emphasis.…”
Section: Discussionsupporting
confidence: 83%
“…Such injuries are likely to have a major economic impact on young families. Similar data has been reported in other regional and international studies on injuries to PAs (1,2,3,4). Preventive measures targeting vulnerable motorcyclist needs emphasis.…”
Section: Discussionsupporting
confidence: 83%
“…These fractures were often open. Frederico Carlos et al [10] , Nirmal Raj Gopinathan et al [11] reported respectively 73.5% and 64% of open fractures in their studies. The proximity of the lower limbs to the ground further exposes them to improvised explosive device explosions, resulting in many associated injuries and traumatic amputations.…”
Section: Discussionmentioning
confidence: 89%
“…Las lesiones vasculares en los miembros inferiores tienen una tasa de amputación general del 11%. Las lesiones de la arterias femoral o poplítea tienen un riesgo de amputación del 28 al 37%, el cual puede incrementar hasta un 70% en las presentaciones tardías 24 - 28 .…”
Section: Complicacionesunclassified
“…Lower extremity vascular injuries have an overall amputation rate of 11%. Injuries of the popliteal or femoral arteries have an amputation risk of 28 to 37%, increasing up to 70% when there is a delay in presentation [24][25][26][27][28] .…”
Section: Complicationsmentioning
confidence: 99%